Pathology of Free-Living Loggerhead Turtle (Caretta caretta) Embryos on the Island of Linosa (Italy) - Frine Eleonora Scaglione; Matteo Cuccato; Erica Longato; Paola Pregel; Daniele Zucca; Stefano Nannarelli; Alessandra De Lucia; Marco Pilia; Elisabetta Manuali; Marco Gobbi; Enrico Bollo; Simonetta Appino (Veterinary Sciences)
On the beach of Linosa Island (Italy), 43 loggerhead sea turtle (Caretta caretta) unhatched eggs were recovered from nests, formalin-fixed and necropsied. The tissue samples were stained with hematoxylin-eosin (HE), Grocott, von Kossa, periodic acid-Schiff (PAS), and Movat pentachrome stains. Histologically, vacuolar degeneration (100.0%) and increased numbers of melanomacrophages (18.6%) in the liver, and edema (14.0%) in the lungs were observed. Twenty-five kidneys (58.1%) showed deposition of blue amorphous material with HE staining, which also appeared PAS-positive and black with von Kossa staining, allowing a diagnosis of calcium oxalate, confirmed by transmission electron microscopy (TEM). The hepatic lesions may be indicative of toxicosis, infection, or a defense mechanism. A statistically significant association between the nest position and renal oxalosis (renal calcium oxalate deposition) was observed. Renal oxalosis was probably due to the exceptionally high summer temperatures, which were statistically higher compared to the temperatures recorded in the previous two years.